Comprehensive experimental evaluation of R1234yf-based low GWP working fluids for refrigeration and heat pumps. (15th April 2022) - Al-Sayyab, Ali Khalid Shaker; Navarro-Esbrí, Joaquín; Barragán-Cervera, Angel; Kim, Sarah; Mota-Babiloni, Adrián
Highlights: R516A, R513A, and R1234yf are compared as alternatives to R134a. The first experimental results of the R516A blend are presented. R513A presents the highest overall system performance by enhancement of 2% in cooling mode. In cooling mode, R516A shows system COP enhancement at low evaporating temperatures ranging from (1 to 15%). Abstract: This work presents an experimental comparison for low GWP refrigerants used in vapour compression cooling and heating systems. The study compares three lower global warming potential (GWP) refrigerants (R513A, R516A, and R1234yf) as drop-in refrigerants to replace the hydrofluorocarbon (HFC) R134a. Measurements are taken from a test rig at different steady-state conditions: for the cooling mode, the evaporating temperature is −5 °C, −10 °C and −15 °C, and is combined with two condensing temperatures (32.5 °C and 40 °C), and different internal heat exchanger (IHX) effectiveness. Besides, in the heating mode, the evaporating temperature is 7.5, 15 and 22.5 °C with five condensing temperatures (55 °C to 75 °C, step of 5 °C). In the cooling mode, R513A presented the highest system COP amongst the low GWP alternatives, increasing up to 8%. R516A shows the lowest system COP at the highest evaporation temperature; however, it exhibits the highest COP and capacity at the lowest evaporation temperature. The IHX positively influences the refrigerating effect for all adopted refrigerants. Regarding the heating mode, R513A presents the highest heating capacity with an average 3% increase, whereas R516A shows the lowest results. R513A shows comparable COP to R134a, especially at higher evaporating temperatures.